Crisis Response in Nursing: A Phenomenological Study of Patient Care Roles During Public Health Emergencies within Thailand’s Border Hospitals - Chantachon, Suratsawadee; Wicharit, Lerkiat; Nak-Ai, Worayuth; Kitphati, Rungrueng; Suphaudomphon, Thira; Krates, Juraporn; Khotmanee, Supaporn (Public Health of Indonesia, 2025)
Background: Nurses play a crucial role in managing COVID-19 patient care by providing nursing services, coordinating with families and medical teams, and preserving healthcare systems' core values. Despite challenges from infection control measures and organizational priorities, nurses remain committed to providing care. Globally, they form the largest component of the health workforce. In Thailand, registered nurses possess extensive knowledge in treating various health conditions and are skilled in managing critical and emergency care. During the COVID-19 pandemic, nurses faced increased workloads and multidimensional responsibilities. Objective: This study explores their lived experiences in managing COVID-19 patient care in Thailand's border hospitals. Methods: A qualitative research using an interpretive phenomenological approach. The key informants were registered nurses involved in the care of COVID-19 patients in Northeastern Thailand's border hospitals. A purposive sampling technique was used, resulting in a total of 12 participants. Data were collected through in-depth interviews, using an interview guide. Diekelmann, Allen, & Tanner's data analysis method was used as the data analysis approach. Results: The results of the study found four themes were identified: 1) Special patient care system, 2) Patient care safety management, 3) Care for critically ill and complex patients, and 4) Resource and equipment management for care. Conclusion: This study highlights nurses' critical role in managing COVID-19 patient care in Thai border hospitals by organizing care systems, ensuring safety, and managing resources. It emphasizes the importance of adaptability, digital tools, and infection control during health emergencies. The findings recommend investing in emergency preparedness, digital healthcare tools, and resource management to strengthen healthcare resilience in future crises.